Interactive Project VIDEOTURO in Enhancing Problem-Solving Skills among Grade 9 students: Video Lesson in Mathematics - Meligrito, Isagani (International Journal of Arts, Sciences and Education, 2011)
This action research aimed to enhance the problem-solving skills of Grade 9 students in mathematics of San Jose national High School. 31 or 55% scored the average and poor level of problem-solving skills performance in the pretest. The researcher addressed in enhancing problem solving skills in Mathematics using the interactive video lesson as an intervention material. The result of the study showed that the number of students who were within a poor level was reduced in the Posttest. There is a significant difference (p=0.030) in the problem-solving level of performance in the posttest results between the modular print (control group) and the recorded interactive video lesson material (experimental group). The findings stressed that the results of the posttest of control and experiment groups have significant differences. It is proposed that teachers should design interactive activities through a recorded video lessons material to promote understanding by having students practice, solve, manipulate reason, and perform amidst the current situation. Recorded interactive video lesson may help student’s visual connections across mathematical skills and concepts and other disciplines. Following the video lesson enhancement material, students should have time to master how to perform problem solving activities. With careful planning, implementation and evaluation, mathematical activities can be achieved successfully by most students.